Metabolic Activity in Human Intermuscular Adipose Tissue Directs the Response of Resident PPARγ+ Macrophages to Fatty Acids - Xiaoying Chen; Sebastian Ludger Schubert; Aline Müller; Miguel Pishnamaz; Frank Hildebrand; Mahtab Nourbakhsh (Biomedicines)
Background/Objectives: Peroxisome proliferator-activated receptor gamma (PPARγ) is a fatty acid-binding transcription activator of the adipokine chemerin. The key role of PPARγ in adipogenesis was established by reports on adipose tissue-resident macrophages that express PPARγ. The present study examined PPARγ+ macrophages in human skeletal muscle tissues, their response to fatty acid (FA) species, and their correlations with age, obesity, adipokine expression, and an abundance of other macrophage phenotypes. Methods: An ex vivo human skeletal muscle model with surgical specimens that were maintained without or with FAs for up to 11 days was utilized. Immunofluorescence analysis was used to detect macrophage phenotypes and mitochondrial activity. Preconfigured arrays were used to detect the expression of 34 different adipokines and chemokines. Results: Data from 14 adults revealed that PPARγ+ macrophages exclusively reside in intermuscular adipose tissue (IMAT), and their abundance correlates with the metabolic status of surrounding adipocytes during tissue maintenance in vitro for 9–11 days. Elevated fatty acid levels lead to significant increases in PPARγ+ populations, which are correlated with the donor’s body mass index (BMI). Conclusions: PPARγ+ macrophages represent a distinctly specialized population of regulatory cells that reside within human IMATs in accordance with their metabolic status. Thus, future in-depth studies on IMAT-resident PPARγ+ macrophage action mechanisms will elucidate the role of skeletal muscle in the pathogenesis of human metabolic dysfunction.